The electoral system - Gonzales Ojeda, Magdiel (2019)
The article carries out a detailed study of the principles, elements and operation of the Peruvian electoral system. This is based on an analysis of the development of the notion of political representation, from its birth in Greek antiquity, to its contemporary development. This is put, then, in relation to the electoral system and the voting forms and rules.